Neurophysiological assessment of brachioradial pruritus patients - Miller, Luiz Henrique Granja Souza Vieira; Akita, Juliana; Martelli, Antonio Carlos Ceribelli; Kirchner, Daniel Rocco; Salgado, Manoel Henrique [UNESP]; Garbino, José Antonio (FapUNIFESP (SciELO), 2021)
Background: Pruritus is a common complaint in dermatology. Wartenberg, in 1943, associated pruritus with neuropathy, relating it to the “posterior antebrachial cutaneous nerve neuropathy”. In 1968, Waisman described patients with frequent pruritus complaints in the upper limb during the summer, which he named “brachioradial summer pruritus”. Currently, this pruritus is named brachioradial pruritus (BRP). BRP is characterized by a chronic pruritus, usually localized, with a long duration, and without apparent cutaneous abnormalities. Neurological disorders both from the central and peripheral nervous systems, including multiple sclerosis, are associated with pruritus. Objective: To investigate correlations between symptomatic dermatomes and alterations in the myotomes, as evidenced by electroneuromyography (ENMG). Methods: Forty-six patients with BRP dermatological diagnoses were subjected to upper limb ENMG. Results: Among 46 patients with C5 to C8 dermatomal pruritus, we evaluated 113 symptomatic dermatomal areas. Overall, 39 (85%) patients had radicular involvement and 28 (60%) had agreement between complaint and the ENMG findings (p=0.015). A total of 80% of the patients with complaints at C7 and 47% at C6 had radicular involvement at the same level. Conclusions: Among the patients who presented complaints, 47 and 80%, respectively, had ENMG alterations in the C6 and C7 myotomes. We conclude that peripheral nervous system involvement is associated with BRP.
Avaliação neurofisiológica de pacientes com prurido braquiorradial
Keywords: Electromyography; Pruritus; Radiculopathy